ADVERBIAL DERIVATION IN TOBA BATAK LANGUAGE: A GENERATIVE TRANSFORMATIONAL STUDY - Esron Ambarita (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2018)
The purpose of this article is to elaborate adverbial derivation in Toba Batak language from the view point of generative transformational study. The data were analysed by applying modified theory with reference to Halle’s model as the main theory.  Therefore, there are six components of sets of generative transformational rules as modified theory in this study, i.e. List of Morphemes, Word Formation Rules, Filter, Orthographic Rules, Phonological Rules, and Dictionary. The method of this study is descriptive qualitative. The data were collected by using observation and interview. The collected data are voice-recordings and writings. The research findings show that adverbial derivation in Toba Batak language are done by attaching (1) prefix [par-], (2) prefix [maN-], (3) prefix [mar-], (4) affix combination [-umal-], and (5) affix combination [-umar-] to stems. The results of the affixation processes generate complex words which have new grammatical and lexical meanings. Phoneme assimilation takes place in morphological processes particularly with prefix [ma-]. The inflectional processes of attaching those affixes bring about phonological idiosyncrasy; therefore, such words must be processed in filter to generate acceptable words in Toba Batak language.